Collaboration for fostering learners’ autonomy in the EFL classroom: Learners’ perceptions and practices (Solukhumbu Multiple Campus Research Journal, 2025)
The study examined the collaborative practices employed in EFL classrooms and their impact on fostering learner autonomy. To investigate the issue, the researcher formulated the following research questions: How do collaborative practices in EFL classrooms contribute to fostering learner autonomy? And what collaborative practices are useful in promoting learner autonomy among EFL students? The qualitative approach was employed in the study. The constructivist paradigm was followed to explore the practices and perceptions. Narrative inquiry was used in the study. Four participants were purposively chosen from one of the constituent campuses of Tribhuvan University, studying in their fourth year of the Bachelor of Education program, and had experience practicing collaboration in classroom activities. The main finding showed that collaborative work enhanced learners’ autonomy. Engagement in groups and collaboration among peers developed confidence and independence among the learners. The study results showed that learners were aware of the final evaluation system, which hindered fostering autonomy. Similarly, they were worried about the work of collaborative partners.